Learning Disability-Adapted Cognitive Behavioural Therapy for Phobia - Liam Alexander MacKenzie Myles (Mediterranean Journal of Clinical Psychology)
Background: Research suggests cognitive-behavioural therapy (CBT) constitutes an effective intervention for phobia. However, literature investigating the effectiveness of CBT for phobia in people with learning disabilities (LDs) is sparse. This case study reports the outcomes of LD-adapted CBT for phobia.